2005
DOI: 10.1007/s11104-004-8070-z
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Aquaporins in Root Responses to Irrigation

Abstract: Due to current environmental issues concerning the use of water for irrigation, the improvement of crop water-use efficiency and a reduction in water consumption has become a priority. New irrigation methods that reduce water use, while still maintaining production have been developed. To optimise these techniques knowledge of above-and below-ground plant physiological responses is necessary. During growth, plant roots are exposed to cycles of wetting and drying in normal rain-fed and irrigation situations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 145 publications
2
43
0
1
Order By: Relevance
“…Such gating of an Arabidopsis aquaporin by changes in pH was recently confirmed in studies of proteoliposomes (Verdoucq et al 2008). Vandeleur et al (2005) hypothesised that gating of aquaporins in roots experiencing O 2 -deficit might be a mechanism by which water uptake is re-directed to other roots in more favourable regions of the soil (e.g. from O 2 -deficient deeper roots, to those in surface layers with access to some O 2 ).…”
Section: Soil Waterlogging -Short Durationmentioning
confidence: 87%
“…Such gating of an Arabidopsis aquaporin by changes in pH was recently confirmed in studies of proteoliposomes (Verdoucq et al 2008). Vandeleur et al (2005) hypothesised that gating of aquaporins in roots experiencing O 2 -deficit might be a mechanism by which water uptake is re-directed to other roots in more favourable regions of the soil (e.g. from O 2 -deficient deeper roots, to those in surface layers with access to some O 2 ).…”
Section: Soil Waterlogging -Short Durationmentioning
confidence: 87%
“…In general PIP1s have little or no water channel activity in vitro, whereas the PIP2s show high water permeability when expressed in Xenopus laevis oocytes (Chaumont et al, 2000). Water permeability of aquaporins can be regulated by cytosolic pH and pCa (Gerbeau et al, 2002;Alleva et al, 2006), phosphorylation (Maurel et al, 1995;Johansson et al, 1998), large pressure pulses (Wan et al, 2004), and osmotic solutes (Ye et al, 2004;Vandeleur et al, 2005). It has been demonstrated that PIP1 and PIP2 members may interact either within the membrane or by targeting to the plasma membrane (Fetter et al, 2004;Zelazny et al, 2007).…”
mentioning
confidence: 99%
“…These resistances are regulated by the physics of conduits (e.g. size and density of vessels), by some physiological traits, such as aquaporin-induced changes of membrane permeability, and depend on the time scale considered (Vandeleur et al, 2005). Directly, through absorption and transport, exceeding part of the cellular barriers, or indirectly, exploring a bigger soil volume and interstices between little agglomerates, the hyphae increase the water flow potentially available to plants.…”
Section: Hydraulic Conductivitymentioning
confidence: 99%